Pengaruh Model Kooperatif Tipe Two Stay Two Stray terhadap Keterampilan Menulis Karangan Eksposisi Siswa SMP - Andhira, Raisya (GERAM: Gerakan Aktif Menulis, 2017)
The purpose of this study is to analyze the effect of the use of cooperative learning model two stay two stray towards the skill level essay writing exposition class VIII SMP Negeri 9 Padang. This type of research is quantitative research with experimental method. The design of this study one group pretest and posttest design. Total population of 224 students. The sample in this research is class student of SMP Negeri 9 Padang VIII.1 by the number of 31 students were determined using purposive sampling technique. In this research there are two variables, namely (1) exposition essay writing skills of students before using cooperative learning model type of two stay two stray and (2) exposition essay writing skills of students after using cooperative learning model type of two stay two stray. The instrument used in this study tests the performance. This research data result score skill tests exposition essay writing class VIII SMP Negeri 9 Padang before and after using cooperative learning model type of two stay two stray. The results of this study based on the t-test, the alternative hypothesis (H_1) received the 95% significance level and degrees of freedom (df) = (N_1 + n_2) -2 because ttable <thitung (1.67 <8.19). In other words, the writing skills essay exposition eighth grade students of SMP Negeri 9 Padang after using cooperative learning model type of two stay two stray better than writing skills essay exposition eighth grade students of SMP Negeri 9 Padang before using cooperative learning model type of two stay two stray. Thus, cooperative learning model two stay two stray can be applied in teaching essay writing skills exposition.